2021
DOI: 10.52455/sbpr.01.202102011
|View full text |Cite
|
Sign up to set email alerts
|

A strong correlation exists between platelet consumption and platelet hyperactivation in COVID-19 patients. Pilot study of the patient cohort from CCH RAS Hospital (Troitsk).

Abstract: It is known that in COVID-19, hypercoagulation and sometimes thrombocytopenia are related to disease severity. There is also controversial data on platelet participation in COVID-19 pathology. We aimed to determine the degree of platelet hyperactivation in COVID-19 patients. Whole blood flow cytometry with Annexin-V and lactadherin staining ("PS+ platelets") was utilized. Additionally, a stochastic mathematical model of platelet production and consumption was developed. Here we demonstrated that the percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Enhanced consumption also increases TPO synthesis by the liver and leads to platelet overproduction and platelets becoming larger and younger in COVID-19 patients [21][22][23]. Our previous in silico studies have additionally demonstrated the important role of these processes in COVID-19 [24]. Above all, mild to intermediate thrombocytopenia was proved to be a negative prognostic marker for COVID-19 patients [20][21][22].…”
Section: Introductionmentioning
confidence: 85%
“…Enhanced consumption also increases TPO synthesis by the liver and leads to platelet overproduction and platelets becoming larger and younger in COVID-19 patients [21][22][23]. Our previous in silico studies have additionally demonstrated the important role of these processes in COVID-19 [24]. Above all, mild to intermediate thrombocytopenia was proved to be a negative prognostic marker for COVID-19 patients [20][21][22].…”
Section: Introductionmentioning
confidence: 85%
“…Finally, models of different phenomena can also be applicable for the studies of ITP. Stepanyan et al [89] have developed a stochastic computational model of platelets' life cycle which takes into the account the consumption of platelets due to COVID-19 thrombosis. Briefly, the platelets are produced in the megakaryocytes from the bone marrow with a TPO level dependent manner.…”
Section: In Silico Approaches To Studies Of Itpmentioning
confidence: 99%
“…After a year of development, SBPReports boasts a highly professional and dedicated editorial board formed by experts in the systems biology field from Belarus, Canada, China, India, Russia, UK and USA. The three major sections of the edition are related to the three major levels of understanding of the biological systems: molecular [1,2], cellular [3,4], and organism [5,6] levels. The papers published in the four issues during this year include original articles [1,2,4,6], reviews [5,[7][8][9], and methodological studies [10,11].…”
Section: Where Do We Stand Now and What Are Our Goals For 2022?mentioning
confidence: 99%
“…The three major sections of the edition are related to the three major levels of understanding of the biological systems: molecular [1,2], cellular [3,4], and organism [5,6] levels. The papers published in the four issues during this year include original articles [1,2,4,6], reviews [5,[7][8][9], and methodological studies [10,11]. In addition, two large abstract collections Systems Biology and Systems Physiology Congress 2021 and International Congress devoted to the Memory of the Founders of Biophysics Department of Physics Faculty of Lomonosov Moscow State Universityprofessor L.A. Blumenfeld and professor S.E.…”
Section: Where Do We Stand Now and What Are Our Goals For 2022?mentioning
confidence: 99%